Microbiota of dental caries in primary teeth of a costa rican child population = Microbiota de la caries dental en piezas primarias de una población infantil costarricense - Tenorio Soto, Keysy 1990-; Gutiérrez Marín, Natalia 1975-; Ramírez Mora, Tatiana 1975-; Altamirano Silva, Pamela 1984- (2024)
The objective of this research was to identify bacteria present in the microbiota of dentinal carious lesions in primary molars of some Costa Rican pediatric patients. Data were collected from 15 children aged between 4 and 8 years old who attended the Pediatric Dentistry Clinic at the Faculty of Dentistry from the University of Costa Rica (UCR). The inclusion criteria were: infants between 4 and 8 years old who presented cavitated carious lesions in primary teeth, who were actively attended by students at the Faculty of Dentistry from the UCR, and whose parents or legal guardians signed the informed consent to participate in this research. Samples were taken using a sterile spoon, placed in storage vials, and subjected to various conventional and molecular microbial identification techniques, such as Gram stain identification, catalase tests, oxidase, TSI, API 20E, API STAPH, and VITEK 2. Of the 60 bacterial strains subjected to Gram staining, the following was obtained: 28 Gram-positive bacteria and 32 Gram-negative bacteria. The main isolated organisms were species of Staphylococcus epidermidis, Pasteurella pneumotropica/Mannheimia haemolytica, Pantoea spp, and Streptococcus mutans.
El objetivo de esta investigación fue identificar las bacterias presentes en la microbiota de lesiones cariosas dentinales en molares primarias de pacientes pediátricos costarricenses. Las muestras fueron recolectadas de 15 niños entre los 4 y 8 años que fueron atendidos en la Clínica de Odontopediatría en la Facultad de Odontología de la Universidad de Costa Rica (UCR). Los criterios de inclusión fueron: pacientes entre los 4 y los 8 años de edad que presentaran lesiones cariosas cavitadas en dientes primarios, que se encuentraran activos para su atención por estudiantes de la Facultad de Odontología de la UCR, y que los padres o encargados legales firmaran el consentimiento informado para participar en esta investigación. Las muestras se tomaron utilizando una cuchareta estéril, colocándolas en viales de almacenamiento y fueron sometidas a diversas técnicas de identificación microbiana convencionales y moleculares tales como: identificación por Tinción de Gram, pruebas catalasa, oxidasa, TSI, API 20E, API STAPH y VITEK. De las 60 cepas bacterianas sometidas a tinción de Gram se obtuvo: 28 bacterias Gram Positivas y 32 bacterias Gram Negativas. Los principales organismos aislados fueron: especies de Staphylococcus epidermidis, Pasteurella pneumotropica/ Mannheimia haemolytica, Pantoea spp y Streptococcus mutans.
En revista Odóvtos, vol. 26, no.1 (enero-abril 2024)
Descripción basada en el contenido visto el 22 de enero, 2025
También disponible en formato HTML y EPUB